Perkembangan Objek Wisata Bahari Air Bangis Kabupaten Pasaman Barat (2010-2017) - Ernovela Ernovela; Siti Fatimah (PAMA Aksara, 2019)
The purpose of this study was to determine the development of Bahari Air Bangis tourism objects in 2010-2017, Sungai Beremas District, West Pasaman Regency. The study was conducted in June-July 2019. This study uses a historical research method consisting of four topics, namely data collection (Heuristics), source criticism, interpretation, and historiography. In addition, data is also obtained through interviews. The results of the study show that there are three aspects that can be seen from the development of the Air Bangis marine tourism object. First, the development of management of the Air Bangis marine tourism potential and attraction, the development of tourism infrastructure supporting facilities, the development of the number of visitors and the role of the community in developing tourism objects. Second, analysis of the supporting factors and obstacles to the development of the Air Bangis marine tourism object. Third, the positive and negative impacts of the development of marine tourism object both in the fields of economy, social culture, environment and so forth. In an effort to develop the Air Bangis maritime attraction, it is inseparable from the cooperation of the regional government with the community around the tourist attraction.